Pelatihan Layanan Prima untuk Santri dan Pengurus Pesantren dalam Mendukung Wisata Ziarah Kubro Internasional - Alfitriani .; Alditia Detmuliati; Yulia Pebrianti; Yoga Aji Nugraha; Debby Fifiyanti; Kiradel Sastra; Nyimas Alysha Nadine Nabilla; Nyanyu Zulfa Nailaturrahmi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
Ziarah Kubro in Palembang City has developed into an international religious tourism destination attended by 25,000-30,000 pilgrims, including tourists from Southeast Asia and the Middle East. However, the increasing number of foreign pilgrims has not been matched by the readiness of human resources to provide services according to international standards. Pondok Pesantren Al-Amalul Khair, which is directly involved in organizing Ziarah Kubro, still provides services informally, unstructured, and not based on the principles of service excellence. This community service activity aims to improve the quality of religious tourism services through service excellence training, the development of Standard Operating Procedures (SOPs), and the strengthening of cross-cultural communication for students and administrators of the Islamic boarding school. The method used is a community-based participatory approach with an action research design, involving 35 participants during three days of training that combines interactive lectures, simulations, role-plays, and direct demonstrations. Data analysis techniques employed qualitative approaches (in-depth interviews, participatory observation, FGDs) and simple quantitative methods (pre-test and post-test). The results showed an increase in participants' understanding of service excellence from only 30% in the good category before the training to 85% after the training. Participants were able to master structured service flow and apply the 5S principles (smile, greeting, polite address, courtesy, and politeness). This activity also successfully produced SOP documents for pilgrim reception, service flow, food safety SOPs, and tourism information media in the form of booklets, leaflets, posters, and digital content. Both hypotheses of the community service activity were accepted, where service excellence training and the implementation of international standard-based SOPs significantly improved the knowledge, skills, and readiness of Islamic boarding school human resources in facing foreign tourists during the implementation of Ziarah Kubro.